Urbanization and growth of slums infrastructure for the urban poor in the city of Bhubaneswar - Mohanty, L.N.P. (2011)
Population explosion in urban areas has posed the problems of inadequate services, infrastructure, housing and also increased the crime rate and pollution. With growing poverty and slums, Indian cities have been grappling with the challenges of making the cities sustainable, i.e., inclusive, productive, efficient and manageable. The sustainability of urban development in India is seen in the context of shelter and slums, basic urban service, financing urban development governance and planning. Rajiv Awas Yojana (RAY) which aims at providing a clean and healthy home to the urban poor would undoubtedly make India a `Slum free' country within a couple of years. Assigning property rights to the slum dwellers and framing a slum policy in the State of Orissa soon, will definitely mitigate the problems of the slum dwellers and address the issue of `housing for all'. - Reproduced.
Keywords: Slums - India - Orissa; Urbanization - India - Orissa; Urbanization